ALAT MEMATIKAN DAN MENGHIDUPKAN TELEVISI DENGAN SHORT MASSAGE SERVICE (SMS) MENGGUNAKAN MIKROKONTROLER ATMEGA 32 - Roziman Roziman; Mesterjon Mesterjon (Jurnal Media Infotama, 2015)
Formulation of the problem is a tool that can make for control or turn on and turn off the TV via SMS. Software used includes operating systems, programming languages and software pengelolah data. The operating system used by Microsoft Windows 7 as the operating system. The programming language used is the programming language Basic - BASCOM AVR. The test is done to test the tool-off tv with this text goes well according to the plan that is when the modem receives a text from the form #Hidup hp then the microcontroller will process the data and gives orders to the tv to live and displayed on the LCD 16 x 2 and as well as command #Mati the tv would dieKeywords: cost of electricity, current sensors